Penyuluhan Gizi Bagi Anak Usia Sekolah Di SDN 07 Rantetayo , Kabupaten Tana Toraja - Hayuti Windha Pagiu; Lucia Yogyana Suramas; Hermin Neli; Adfryanty Tandirerung (jurnal ABDIMAS Indonesia, 2023)
School-age children are children aged between 6 and 12 years and are one of the groups of children who are vulnerable to nutritional problems (Ulpa et al., 2018). Poor nutritional status in children will affect physical growth, mental development and thought processes which will impact their production power and work ability as adults (Wicaksana & Nurrizka, 2019). The aim of this service activity is to increase students' knowledge about the importance of nutrition for school-aged children to support the growth and development of school-aged children to prevent nutritional problems in school-aged children, for this reason it is necessary to carry out health promotion efforts in the form of providing education and evaluation to increase knowledge. about nutrition so that it can increase awareness of school-age children in maintaining health.